Structure and tree diversity in oak forests of central Mexico - Rosaliano Evaristo, Rubén; Ávila-Akerberg, Víctor; Franco-Maass, Sergio; Valencia-A., Susana; López Mathamba, Luis Angel (Instituto de Ecología, A.C., 2022)
The structure and tree diversity of oak forests in two micro-watersheds in central Mexico were characterized. The diameters (≥ 5 cm) and heights of the trees in circular plots of 1000 m2 were measured. The horizontal structure was analyzed based on the value of relative importance (VIR); the diameters of six species shared at both sites were compared with the Mann-Whitney test, and the Pretzsch A index was used for the vertical structure. For alpha and beta diversity, PAS 4.3 software was used. In both cases Quercus laurina and Quercus rugosa obtained the highest values of density, dominance, and VIR; although there are no differences between the diameters, young specimens predominate (diameters 5 - 23 cm) and present a typical distribution of an inverted J, frequent in naturally regenerating forests. However, Quercus crassipes shows a decrease in individuals (< 15 cm), which suggests possible displacement. The vertical distribution indicates that the height is distributed mainly in stratum III (< 15 m). In terms of diversity, the difference is not significant, although the specific richness was 22 and 12 species in CPG and CRP, respectively, and there was? an intermediate replacement. The results of this work contribute to understanding the ecological processes of structure, diversity, and interaction between tree populations in these communities, so it is necessary to monitor especially species with behaviors such as Q. crassipes.